Prevalence and variance of shoulder injuries in elite collegiate football players - Kaplan, L. D.; Flanigan, D. C.; Norwig, J.; Jost, P.; Bradley, J. (The American Journal of Sports Medicine, 2005)
Background: Shoulder injuries are the fourth most common musculoskeletal injury encountered in American football players. There is little information in the literature on the role of playing position in the type of shoulder injuries seen.